Fibrocartilaginous Embolism Associated with the Extrusion of the Intervertebral Disc in a Dog - Chaves, Rafael Oliveira; Copat, Bruna; Beckmann, Diego Vilibaldo; Feranti, João Pedro Scusssel; de Oliveira, Marília Teresa; Corrêa, Luís Felipe Dutra; Ripplinger, Angel; Mazzanti, Alexandre (Acta Scientiae Veterinariae, 2016)
Background: Intervertebral disc disease is a usual neurological disorder in dogs, which the spinal cord is compressed by intervertebral disc extrusion or protrusion. Fibrocartilaginous embolic myelopathy isan acute infarction disease of spinal cord caused by fibrocartilaginous emboli histologically identical to the nucleus pulposus of intervertebral discs. The aim of this report is present two cases of fibrocartilaginous embolic myelopathy in dogs with intervertebral disc disease. Cases: Two dogs - dachshund breed - were referred to the Veterinary Medical Teaching Hospital of the UFSM. In the first case, the dog was three years old and the owner described complete inability to move the pelvic limbs. The neurological examination revealed paraplegia, postural reactions deficits, normal spinal reflexes and muscle tonus in the hind limbs, pain on palpation in T12-T11 region and loss of deep pain in hind limbs. In the other case, the dog was seven years old and the owner described partial inability to move four limbs. The neurological examination revealed non-ambulatory tetraparesis, postural reactions deficit, normal spinal reflexes in four limbs and pain on palpation in cervical spine. In both cases, the presumptive diagnosis was intervertebral disc disease and surgical treatment was indicated. The dog with thoracolumbar injury died during the anesthesia and the dog with cervical injury was euthanized, after decision of owner. During the necropsy was observed intervertebral disc extrusion between L1-L2 vertebrae in a dog and between C3-C4 vertebrae in the other case with cartilaginous fragments in the spinal canal. Histopathology revealed marked diffuse necrosis with multifocal hemorrhage and cartilaginous emboli. Discussion: Fibrocartilaginous embolic myelopathy is commonly reported in large and giant breed dogs, though also occur in small and medium-sized breeds of dogs. One hypothesis is the pulpous nucleus remains soft for a longer period in large breed dogs, empowering to infiltration in the spinal cord vessels. The intervertebral disc extrusion occurs predominantly in dogs with age between three and six years old, in the cervical, thoracolumbar (T11-L3) and lumbar regions. Chondroid or fibroid degeneration of the intervertebral disc is the most common cause of spinal cord compression in small animals. In chondrodistrophic breed dogs is frequently chondroid degeneration, which the nucleus pulposus moves into the spinal canal through rupture of the annulus fibrosus (extrusion or Hansen type I), causing acute spinal cord compression. The prevalence of fibrocartilaginous embolism in adult and old dogs increase the possibility of predisposing factors, facilitating the injection intravascular of nucleus pulposus material. One of the most accepted theories about the mechanism of fibrocartilaginous emboli into the vessels is due to increase of inside discal pressure and liberation of fibrocartilaginous emboli from nucleus pulposus into the vertebral artery for retrograde flow, reaching the spinal cord by blood flow. The simultaneous occurrence of intervertebral disc disease and the infarction of spinal cord in the proximate region accentuate the hypothesis that the etiology of fibrocartilaginous embolic myelopathy is mechanical into the vessels of the spinal cord. Keywords: neurology, spinal cord, intervertebral disc disease, dogs.